Implementation of Marketing Management Education in Developing the Image of Madrasahs - Arianto, Erwin; Chamami, M Rikza; Muchith, Saekan (Jawda: Journal of Islamic Education Management, 2025)
This study aims to describe the implementation of educational marketing management in developing the image of Madrasah Aliyah Negeri (MAN) 2 Semarang City. The research employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings reveal that: (1) the stages of educational marketing implementation were effective in attracting new students, including high-achieving ones; (2) the success of marketing was closely linked to public recognition of the madrasah’s quality, as reflected in the increasing number of applicants and positive student feedback; and (3) supporting factors included visionary leadership, teacher competence, and the involvement of alumni and school committees, while inhibiting factors consisted of limited digital literacy, ineffective communication, and negative stereotypes about madrasahs. The implications of this study emphasize that well-planned educational marketing management can enhance the competitiveness of public madrasahs and serve as a model for institutional development in the context of contemporary educational challenges.